(untitled) (Global Journal of Science Frontier Research, 2012)
The present investigation was undertaken to study the combining ability for egg production traits using the line x tester mating design. Four local male lines (Baheij, Bj; Matrouh, Mt; Silver Montazah, SM and Golden Montazah, GM) and two commercial female testers (Lohman Brown, LB and Lohman Selected Leghorn, LSL) were used in this study. Combining ability estimates are important genetic attributes to chicken breeders in predicting improvement via hybridization and selection programs. The magnitude of specific combining ability (SCA) variance was evident from mean squares, indicating that egg production traits had been controlled by non-additive genes. However, among the four male lines, Silver Montazah (SM) showed maximum general combining ability (GCA) effects for number of eggs at 90 d., of laying (EN1), number of eggs at 180 d., of laying (EN2), number of eggs at 240 d., of laying (EN3), number of eggs till 52 wks., of laying (EN4), average egg weight at 52 wks., of laying (EW4) and egg mass throughout 52 wks., of laying (EM) studied traits. The second high GCA scoring parent for EN1, EN2, EN3, EN4, EW4 and EM was GM parental line.